Values and ethics in coaching - Iordanou, Ioanna; Hawley, Rachel; Iordanou, Christiana (Thousand Oaks, CA SAGE Publications Ltd, 2017)
The first complete guide to exploring values and ethics in coaching, this book will guide you through the responsibilities of coaching practice, and help you recognize and reconcile common ethical dilemmas and choices. Part I explores the theory and research underpinning ethical coaching practice, and invites you to examine own personal and professional values. Part II delves into the key ethical considerations in the coaching relationship, including contracting, confidentiality and understanding boundaries. It explores each issue in depth, and offers implications and suggestions for practice. Part III examines individual professional contexts, including coaching in business, sports and healthcare with real life examples and reflections from practicing coaches. This book is vital reading for trainee and practitioner coaches, and those looking to introduce ethical coaching practice into a professional setting.
Introduction -- Part I: The Nature of Values and Ethics -- Chapter 1: What are Values and Ethics? -- Chapter 2: Understanding Personal and Professional Values -- Part II: Ethical Practice -- Chapter 3: Developing the Coaching Relationship -- Chapter 4: Maintaining an Ethical Coaching Practice -- Chapter 5: Developing an Evidence-Based Coaching Practice -- Chapter 6: Practising Reflexively -- Chapter 7: Coaching across Professional Boundaries and Contexts -- Part III: Ethical Issues in Coaching Contexts -- Part III: Ethical Issues in Coaching Contexts -- Chapter 8: Ethical Issues in Business Coaching -- Chapter 9: Ethical Issues in Coach Education and Training -- Chapter 10: Ethical Issues in Sports Coaching -- Chapter 11: Ethical Issues for Coaching in Healthcare -- Conclusion: Towards a Shared Understanding of Ethical Standards
Includes bibliographical references (pages [187]-202)and index.
Keywords: Coaching (Athletics) -- Moral and ethical aspects; Personal coaching -- Moral and ethical aspects